“Estudio de factibilidad para la creación de una microempresa dedicada a la elaboración y comercialización de trenza prendefuegos en la ciudad de Quito” - Verduga Mejía, Lourdes Maribel (2013)
The following document is about to the new company creation which elaborates and trades trenza prendefuegos in Quito – Ecuador. This new product is able to initiate a flame in a safety way and avoid home accidents, because, many people used to burn flame with dangerous liquids, such as: gasoline, alcohol, and other combustibles. The development of this investigation was realized in some supermarkets, books, people and INEC. All these elements support the information revealed in this document. The first chapter features the background about this new product, objectives, research methodology. The second chapter contains market research, features identification of the product, the offer and demand in the marked, marketing strategies.